2012
DOI: 10.1111/j.1471-6712.2012.01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare personnel’s experiences of situations in municipal elderly care that generate troubled conscience

Abstract: Healthcare personnel may perceive troubled conscience when feeling inadequate and powerless. It is important to further explore healthcare personnel's descriptions of situations in daily work, which generate troubled conscience to increase the awareness of such situations. This study aimed to describe health care personnel's experiences of situations in municipal elderly care that generate troubled conscience. In this qualitative study, interviews were conducted with Registered and Enrolled nurses and nursing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 34 publications
3
80
0
9
Order By: Relevance
“…This is especially true during nights with fewer personnel. 33 It is important to provide information to patients regarding when and how to reach home health care staff, as well as what type of services home health care can provide.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true during nights with fewer personnel. 33 It is important to provide information to patients regarding when and how to reach home health care staff, as well as what type of services home health care can provide.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Norell Pejner, Ziegert, and Kihlgren (2012) showed that although nurses considered giving emotional support to older people important, and knowing when it is needed as part of their professional skill set, work conditions did not always allow time for that. Ericson-Lidman, Norberg, Persson, and Strandberg (2013) showed that health care personnel were troubled by conscience when caught between various demands, rules, and recommendations that did not benefit the older people; they felt unable to relieve suffering and provide proper care to their patients. This indicates that being unable to work and act according to one’s values could create a feeling of guilt among professionals and promote neither good encounters nor good relations.…”
Section: Introductionmentioning
confidence: 99%
“…20 Another study confirmed the finding that nurses often feel caught in a difficult position between patients and doctors. 17 In addition, a review on quality improvement in care homes, which focused on the management of specific physical health needs, argued that structured interventions in shared planning are necessary. 21 The current study reveals a picture of varying quality in care.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%